METHODS OF USING MAPS IN TEACHING THE 9TH GRADE COURSE OF ECONOMIC AND SOCIAL GEOGRAPHY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
One of the most important goals of geography and social science courses is to have the ability to read, analyze, and understand maps. In social science education, there are many topics related to maps and the concepts of maps. Geographic location is one of the most important topics. The purpose of this study is to assess the knowledge of undergraduate students about their geographical location. For this purpose, research was conducted on questions and activities related to geographical location and related concepts. The study explains the details and results of the research conducted by students.